Leaders' Coping Mechanisms in Facing Pressure During Organizational Transformation - Pramesti, Paramita; Suryanto, Suryanto (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study examines the experiences of two leaders who guided their organizations through significant transformations. Through an examination of the challenges faced, perceptions formed, and coping strategies employed, the research highlights the multifaceted nature of organizational change. Using a qualitative case study approach, the study draws on in-depth interviews with the leaders, complemented by manual thematic coding and theoretical analysis. Findings reveal that both leaders experienced initial emotional distress but successfully managed stress through a combination of coping mechanisms, namely self-regulation, emotional-based coping, and problem-based coping can help manage disruptive situations, transform work overload into people development, improve productivity, and bring credit to the organization. The study underscores the importance of leadership in navigating organizational change and underscores the positive impact of effective coping strategies on individual and organizational outcomes.